POETRY OF YAKOV SHCHOLEV IN THE LITERARY-CRITICAL RECEPTION OF ANATOLIY POGRIBNY - Torak, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article analyzes the canvas of Yakov Shchogolev's poetic creativity and life on the basis of Anatoly Pogribny's literary-critical essay, published in 1986, the most complete in terms of coverage of the source base and little-known to a wide range of archival materials about the native of Okhtyrka. The problem of returning from oblivion and deepening various kinds of information about the figure of Yakov Shchogolev in modern literary studies remains relevant today, since even during his lifetime the poet was on the verge of interest from his contemporaries. The presented research aims to draw a portrait of Yakov Shchogolev and his creative heritage on the basis of the literary-critical reception of the poetic acquisition of the «late romantic» by an authoritative researcher. The methodological basis involves the use of biographical, descriptive methods in the work process, as well as methods of analysis and hermeneutics of the text as basic ones. The scientific novelty of the article lies in the fact that the figure of Yakov Shchogolev is systematically and generally highlighted, under the optics of the vision of an authoritative researcher, literary critic and literary scholar Anatoly Pogribny. An element of polemic with individual judgments of the literary scholar is also included. Practical significance, obtained results and prospects for further studies. As a result, the poetics and literary portrait of Yakov Shchogolev are analyzed against the background of the postmodern era through the prism of Anatoly Pogribny's reception.